LINGKUNGAN FISIK DAN KEKAYAAN MIKROALGA DI DANAU UNIVERSITAS TERBUKA, TANGERANG SELATAN - Budi Prasetyo (Jurnal Matematika Sains dan Teknologi, 2013)
Lake of Open University (UT) is designed not only as a container, watershed, irrigation, sports, and recreation, but also as critical habitat for the survival of plants and aquatic animals ranging from algae groups to types of vertebrate. Information relating to the data microalgae and environmental conditions of lake UT physical and chemical have not been investigated. Research objectives were to measure the wealth of microalgae that live in Lake UT, the microalgae diversity, and the physical and chemical environment. The method used to identify each kind of microalgae, is by counting the number of individuals microalgae, and analyze the water quality. Measurement results showed that the brightness of the physical environment of the lake water had turbid category (52-60 cm). The temperature of the lake water showed 31 to 31.5 oC, this temperature range is good for the growth of microalgae. Value of the degree of acidity of water was 7.3 to 7.5. DO measurements generating valued from 0.5 to 0.57 mg/L. The wealth of microalgae that live in lake UT was identificated as many as 21 genera at four stations with a total population of 4.080 individual/mm3. The highest percentage individual was Scenedesmus sp. Species richness index was 3,33 (medium category). Highest individual density was found in th middle of the lake by 4.651 individualLitre, followed by a passage from edge of the lake to the edged of gazibu (2.318 individual/Litre), the edge of lake (2.025 individual/Litre), and the last outlet (1.193 individual/Litre) lake. Biodiversity index is quite low at 2.107. Desain pembuatan danau UT di samping sebagai tempat resapan air, wahana rekreasi, sarana olahraga, juga merupakan habitat penting bagi tumbuhan dan hewan air (golongan alga sampai jenis vertebrata). Informasi mengenai data mikroalga serta kondisi fisik dan kimiawi lingkungan danau UT belum diketahui sehingga perlu dilakukan penelitian. Tujuan penelitian untuk mengukur kekayaan mikroalga, keanekaragaman mikroalga, dan kondisi lingkungan fisik dan kimiawi. Metode yang digunakan adalah mengidentifikasi setiap jenis dan menghitung jumlah individu mikroalga, serta menganalisis kualitas air. Hasil pengukuran kecerahan air danau dikatakan relatif keruh (52-60 cm). Pengukuran suhu air menunjukkan besaran angka 31-31,5oC, kisaran suhu tersebut baik bagi pertumbuhan mikroalga. Nilai derajat keasaman air adalah 7,3-7,5, sedangkan hasil pengukuran DO sebesar 0,5-0,57 mg/L. Kekayaan mikroalga yang teridentifikasi di danau UT sebanyak 21 genus ditemukan di empat stasiun dengan total populasi 4.080 individu/mm3. Persentase jumlah individu terbanyak adalah Scenedesmus sp. Indeks kekayaan jenis termasuk kategori sedang (3,33). Kepadatan individu tertinggi ditemukan di stasiun-2 (bagian tengah) sebesar 4.651 individu/Liter, selanjutnya diikuti oleh stasiun-3 dari tepi danau sampai tepi gasebo (2. 318 individu/Liter), stasiun-1 di bagian tepi danau (2.025 individu/Liter), dan stasiun-4 di bagian keluaran air (1.193 individu/Liter). Indeks biodiversitas jenis cukup rendah yaitu 2,107.